PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM MELAKUKAN TRANSAKSI ELEKTRONIK DI INDONESIA - Bintang Evitayuni Purnama Putri, A. A.; Lamury Hadjon, Edward Thomas (Kertha Semaya : Journal Ilmu Hukum, 2014)
Electronic transaction is a legal act performed by using a computer or other electronic media. Breaches of electronic transaction to be made good with applicable laws and regulations. The purpose of writing this paper is that consumers know the remedy electronic transaction in the travel and forms of legal protection of the consumers electronic transaction. This paper uses the method of normative legal research. Remedies that can be in use when consumers get the goods that do not comply is through the courts and out of court, legal protection of consumer electronic transaction contained in law Number 8 of 1999 on cosumer protection and in the law Number 11 of 2011 on information and electronic transaction.
Keywords: E- commerce transaction , efforts law, consumers protection